PERAN GURU SEBAGAI FASILITATOR DALAM MENINGKATKAN KEMANDIRIAN BELAJAR SISWA SEKOLAH DASAR - Tambunan, Maryana; Tasha Wulandari; Dwi Diki Junior (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Education has an important role in creating quality human resources to support the progress of a country. For this reason, professional teachers are needed who not only teach, but also act as facilitators who create conditions that support students' learning independence. Teachers must prepare appropriate facilities and infrastructure and adapt learning methods to the character and needs of students. In addition, building positive relationships with students and parents and providing motivation are also important to increase students' enthusiasm for learning. Learning independence is essential for developing skills such as time management and problem solving. This research uses a descriptive qualitative approach through literature study to analyze the role of teachers in supporting students' learning independence. Data were collected from various reliable literature sources and analyzed using content analysis. The results show that the role of teachers as facilitators is very important in creating a learning atmosphere that supports student independence, although challenges in developing learning independence still exist. Further research is recommended using empirical qualitative methods, such as in-depth interviews and direct observation, to gain a deeper understanding of the educational realities faced by teachers.